Measuring Uniocular Fields of Rotation: Modified Goldmann Perimetry Versus Aimark Perimetry. (September 2014) - Hanif, Sahira; O'Connor, Anna; Rowe, Fiona
Abstract Aim: The quantification of ocular rotation in clinical practice is important, with a number of methods of assessment. However, there is little consensus on which method is most reliable and a lack of comparative data for these methods. The aim of this study was to directly compare the modified Goldmann and Aimark methods in subjects with full ocular motility. Methods: This was a prospective cross sectional study to compare the extent of uniocular fields of rotation measured by the Aimark and the modified Goldmann perimeters. The inclusion criteria were full ocular motility and unaided logMAR visions of 0.2 or better in each eye. The results for the four cardinal positions of gaze (right, left, up and down gaze) were analysed and comparisons made with Bland Altman analysis. Results: 108 subjects were recruited. The mean ocular rotations for abduction, elevation, adduction and depression were 69.9° ± 12.8°; 57.8° ± 12.6°; 61.6° ± 10.1° and 68.6° ± 10.5° respectively for the Aimark and 54.4° ± 8.6°; 47.3° ± 8.3°; 53.3° ± 8.6° and 59.5° ± 9.1° respectively for the modified Goldmann. The Aimark recorded higher ocular rotations for all positions of gaze in comparison to the modified Goldmann. The Aimark method tested twelve axes per eye and the modified Goldmann tested 8 axes per eye. However the Aimark was quicker per axis (RE: 11.7 ± 4.9 seconds; LE: 11.5 ± 5 seconds) in comparison to the modified Goldmann (RE: 13.4 ± 10.6 seconds; LE: 13.1 ± 10.6 seconds). Conclusion: The results between the two tests are not interchangeable. The Aimark method measures greater ocular rotations with a supra-threshold compared to the Goldmann measures with a foveal threshold fixation target.